(untitled) (Applied Biological Research, 2024)
The use of synthetic carotenoids in fish feed to potentiate the colouration, along with some health benefits has become exorbitant to mitigate the demand for lucrative ornamental fish within budget. Switching the source of pigmentation and colouration from synthetic to natural sources is all time preferable choice for biological system as well as for fish farmers. Petal dust of Asian pigeonwings (Clitoria ternatea) was incorporated in basal diet to retain the colour of rosy barb (Pethia conchonius) within captive conditions. Varied concentrations of petal dust(0.5, 1.0, 1.5 and2 g 100 g-1 basal feed) were added to the basal feed, fed twice a day at 4% body weight. Water quality parameters and proximate analysis of feed and growth parameters were measured and carotenoid concentration in fish tissue were measured spectrophotometrically. At the completion of 60 day’s experiment a spectacular increase in growth, survival, and carotenoid concentrations (1.88 to 2.42 µg g-1) in body tissue was observed. The best survival and growth of fish were obtained from D4 (0.5%) at 5% level of significance. In proper captive conditions, it is recommended to include 0.5% Asian Pigeonwings dust in prepared feed for better growth and colour retention of rosy barb.